Advancement of practice and use of medication adherence technologies - Tadić, Ivana; van Boven, Job; Tsiligianni , Ioanna; Potočnjak , Ines; Mihajlović, Jovan; Dima, Alexandra Lelia; Nabergoj Makovec, Urška; Agh, Tamas; Kardas, Przemyslaw; Ghiciuc, Cristina Mihaela; Petrova, Guenka; Bitterman, Noemi; et al. (Archives of Pharmacy, 2022)
Medication non-adherence is recognized as a global problem associated with financial burden for patients and healthcare funds. At the European level, different Medication Adherence Technologies (MATech) are in use. The European Network to Advance Best practices and technoLogy on medication adherencE (ENABLE, COST Action 19132) was launched to: 1) identify current practices for Medication Adherence (MA) support by healthcare professionals; 2) create a structure for the repository of existing MATech that could be used by different stakeholders; and to 3) prepare guidance for sustainable implementation of MATech across European healthcare settings. ENABLE gathered different healthcare professionals and academics from 39 countries, to achieve the set of goals during a four-year period. Several cross-European studies were conducted employing stakeholder consultation (Delphi) and survey methods, including analysis of current practices for assessing and supporting MA in routine care, as well as barriers and facilitators to managing MA, work on medication management during COVID pandemic, reimbursement pathways of adherence interventions and protocols to identify the best practices and technologies. The MATech repository was designed by ENABLE members, and consultation of different stakeholders is currently in progress. The repository structure includes information about the MATech product and provider, goals and content related to managing MA, and information about the scientific evaluation and implementation. A cross-European expert survey identified a limited number of MA enhancing interventions that are currently subject to reimbursement. ENABLE identified the need for collaboration, infrastructure, and reimbursement to enhance the uptake of MATech in daily practice.